2020
DOI: 10.2217/fvl-2020-0202
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Procoagulant Microvesicles in Patients With Dengue Fever

Abstract: Background: The levels of procoagulant microvesicles (MVs) and tissue factor (TF)-bearing MVs may be increased in many conditions, including dengue fever (DF). This study aimed to measure the levels of MVs and TF-bearing MVs in patients with DF and matched healthy controls. Materials & methods: Levels of MVs and TF-bearing MVs in the plasma of patients with DF and matched healthy controls were measured using functional assay. Results: The patient group had significantly elevated levels of MVs (p < 0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 42 publications
0
8
1
Order By: Relevance
“…The current study shows elevated levels of procoagulant MVs in the patient group as compared to healthy controls. Elevated MVs have been reported in COVID-19 infection 18–23 lung diseases, 33 other viral diseases, 17 and inflammatory conditions, 13 which have been associated with tendency for thrombosis. Interestingly, elevated levels of MVs derived from endothelial cells and platelets have been reported in COVID-19 with malignancy as compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The current study shows elevated levels of procoagulant MVs in the patient group as compared to healthy controls. Elevated MVs have been reported in COVID-19 infection 18–23 lung diseases, 33 other viral diseases, 17 and inflammatory conditions, 13 which have been associated with tendency for thrombosis. Interestingly, elevated levels of MVs derived from endothelial cells and platelets have been reported in COVID-19 with malignancy as compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue factor is the principal activator of the coagulation cascade, which is another procoagulant player. 46 , 47 Although TF is normally found in the sub-endothelium matrix and TF is sequestrated from the circulation, some studies have demonstrated that TF-bearing MVs 13 , 17 or soluble TF 48 , 49 can be found in the blood circulation in many inflammatory diseases. Elevated levels of TF and increased TF patient with COVID-19 compared to non-COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CXCR4 expressing platelets can transfer CXCR4 to CXCR4 negative cells through membrane fusion [89], indicating a role of PMVs in X4 HIV-pathogenesis (Figure 3). DENV activates platelets via CLEC2, leading to PMV release, which typically exist at elevated levels in patient plasma with procoagulant activities [29,90]. These PMVs are shown to enhance macrophage and neutrophil effector functions, including neutrophil extracellular trap (NET) formation and pro-inflammatory cytokine release (Figure 3) [29].…”
Section: The Role Of Pmvs In Viral Infectionsmentioning
confidence: 99%